Real-time and selective detection of nitrates in water using graphene-based field-effect transistor sensors. Issue 8 (5th July 2018) - Chen, Xiaoyan; Pu, Haihui; Fu, Zipeng; Sui, Xiaoyu; Chang, Jingbo; Chen, Junhong; Mao, Shun
Abstract : A benzyltriethylammonium chloride-modified graphene field-effect transistor sensor has high sensitivity, high selectivity and rapid response for nitrate detection. Abstract : Nitrate, the main form of dissolved nitrogen, is one of the key factors causing water eutrophication. Conventional detection methods are unsuitable for real-time and in situ monitoring of nitrates because they need chemical reagents for sensing and are time-consuming. Here we report a novel nitrate sensor based on a field-effect transistor (FET) device. With reduced graphene oxide (rGO) nanosheets as the FET channel material, the sensor uses benzyltriethylammonium chloride (TEBAC) as a capture probe which has been modified on the rGO surface. The rGO/TEBAC sensor exhibits an ultra-low detection limit of 1.1 μg L −1 NO3 -N with a rapid response within 2–7 s, which is superior to that of most commonly used sensors and far lower than the threshold concentration of total nitrogen (0.3 mg L −1 ) for water eutrophication. This simple and miniaturized sensor also shows high selectivity over other anions such as Cl −, SO4 2− and CO3 2− . Our study provides a new strategy for rapid, sensitive, and selective detection of nitrates, which is promising for real-time and in situ water quality monitoring.